ANALISA RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNING DAN CAPITAL SEBAGAI ALAT UNTUK MENGUKUR TINGKAT KESEHATAN BANK : STUDI KASUS PADA BANK PEMERINTAH YANG TERDAFTAR DI BEI TAHUN 2011-2013 - Santoso, Cahyo Budi (Universitas Riau Kepulauan, 2014)
This study aims to determine the soundness of government banks listed on the Stock Exchange in the period 2011-2013 by using the method of valuation of the bank is the method of Risk - Based Bank Rating ( RBBR ) in accordance with the Circular Letter No. 13/24 / DPNP October 25, 2011 which is described by RGEC. RGEC consists of Aspects Risk (Risk), Aspects of Good Corporate Governance (GCG ), Aspects of Earnings and Aspect Capital . This study was a descriptive study quantitatively by calculating the ratio existing in the aspect of risk (LDR and NPL ), aspects of GCG ( ROE and NPM ), aspects of earnings ( ROA and NIM ), and aspects of capital ( CAR ).Â This study uses data publication of annual financial statements of state banks listed on the Stock Exchange from 2011 to 2013 , namely PT . Bank Mandiri , PT . Bank Rakyat Indonesia , PT . Bank Negara Indonesia and PT . State Savings Bank . It can be concluded that the performance of state -owned commercial banks in good shape . This is evident from the calculated ratio is in accordance with the provisions stipulated by Bank Indonesia .Â Based on the research that has been done that overall during the 2011-2013 four state-owned commercial banks have a healthy level of healthÂ Keyword : health of the Bank , Commercial Bank Owned Government , Risk Based Bank - Rating , Registered in Indonesia Stock Exchange